Communication patterns cares for children and Deli river in building the moral of children in the River - Insani, Sima; Adhani, Abrar (Universitas Ahmad Dahlan, 2022)
A group of people who have the same goals and vision will form a group. A group can be used as a forum to communicate and exchange ideas and information. In exchanging information, ideas, and ideas some patterns have been agreed upon by the group. This study aims to determine the communication patterns formed by the Child Care Community and the Deli River in building children's morale on the riverside. This research uses a descriptive qualitative approach by collecting data through observation, in-depth interviews, and literature study. The results showed that there were forms of communication patterns from the child care community and the Deli River in building the morale of the children on the riverbank, with various patterns of one-way communication, two-way communication.